2013
DOI: 10.1007/978-1-62703-505-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Connexins in Restenosis After Balloon Injury

Abstract: Atherosclerosis is an arterial progressive disease characterized by accumulation of lipids, macrophages, T lymphocytes, and smooth muscle cells in large- and medium-sized arteries. Erosion and rupture of the atherosclerotic plaque may induce myocardial infarction and cerebrovascular accidents that are responsible for a large percentage of sudden death. Atherosclerosis is often treated by angioplasty generally followed by stent implantation. Although angioplasty and stent implantation are necessary for the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…They are closely associated with vascular function. Connexins (Cxs) are the main components of GJs, and Cx43 is expressed mostly in the vascular wall [ 16 , 38 ]. Previous studies have indicated that Cx43 in vessel wall increased after PCI and played a promoting role in vascular remodeling by encouraging VSMCs to proliferate and be activated together, leading to inflammation in injured vessels [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are closely associated with vascular function. Connexins (Cxs) are the main components of GJs, and Cx43 is expressed mostly in the vascular wall [ 16 , 38 ]. Previous studies have indicated that Cx43 in vessel wall increased after PCI and played a promoting role in vascular remodeling by encouraging VSMCs to proliferate and be activated together, leading to inflammation in injured vessels [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This report considers the vascular connexins Cx37, Cx40, and Cx43 (Larson et al, 1990;van Rijen et al, 1998). Cx40 and Cx37 are expressed in all vascular endothelia, and Cx43 is expressed in the endothelium of larger arteries and in arterial bifurcations (Saez et al, 2003;Sandow et al, 2003;Morel and Kwak, 2013;Morel, 2014). Cx43 is mainly expressed in VSMCs (Saez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%